Analysis on feasibility of a novel cryogenic heat exchange network with liquid nitrogen regeneration process for onboard liquefied natural gas reliquefaction. (December 2020) - Wang, Zhe; Han, Fenghui; Ji, Yulong; Li, Wenhua
Abstract: Flexibility and compact multi-stream heat exchange process with cryogenic heat exchange network (CHEN) and liquid nitrogen regeneration refrigeration system (LN2 ReS) was proposed for onboard liquefied natural gas (LNG) reliquefaction. LNG circulates heat exchange with liquid nitrogen through recuperator, precooler, and subcooler successively in the CHEN to become supercooled LNG. Then it sprayed from the upper part into the storage tank to cool its boil off gas (BOG). To achieve the purpose of BOG reliquefaction in the tank. Based on the reverse Brayton nitrogen cycle, the nitrogen is regenerated into liquid nitrogen by an economizer, compressor, cooler, and expander in turn for storage and the next heat exchange. Measured the heat transfer result of 20 kW cold capacity, and found that the proposal has the characteristics of compact structure, no freezing, simple control logic, efficient pre-cooling liquefaction, etc. It only needs to control the design freedom of the flow rate of the LN2 ReS, which can be adapted to the LNG reliquefaction process. Besides, the exergy loss of the proposed CHEN accounts for 30.3% of the total, which is less than the proportion of the LN2 ReS. After process calculation, experimental case study, and exergy loss analysis, it proves the feasibility of the proposal and is particularly suitable for new energy ships.